India's foreign policy: a reader/ edited by Kanti P. Bajpai and Harsh V. Pant - "Bajpai, Kanti P. (ed.);Pant, Harsh V. (ed.)" (New Delhi, 2013)
In this timely volume two leading experts on India's foreign policy bring together essays written over the last 15 years. The volume explores several myths about the country's foreign policy that it lacks a strategic culture; that is formulated without any clearly discernible guiding principles; and that is largely idealistic in its orientation.
Keywords: India-Foreign policy